2017
DOI: 10.1007/s00253-017-8585-x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and membrane topologies of the iron-containing ω3 and ω6 desaturases from Mortierella alpina

Abstract: Polyunsaturated fatty acids (PUFAs) are essential lipids for cell function, normal growth, and development, serving as key structural components of biological membranes and modulating critical signal transduction events. Omega-3 (n-3) long chain PUFAs (LC-PUFAs) such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been shown to protect against inflammatory diseases and enhance brain development and function. This had led to a marked increase in demand for fish and fish oils in human diets, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
8
2
Order By: Relevance
“…Substrate preference was an exciting topic determined by the structure and amino acid in the enzyme's binding site. Scientists found that Δ15-desaturase from Riftia pachyptila ( 72 ) and M. alpina ( 73 ) show a preference for C18 fatty acids, while Δ17-desaturase from Pythium aphanidermatum ( 74 ) display a higher catalytic activity for C20 fatty acids ( Table 3 ). On combining site directed mutagenesis, homology modeling, and molecular docking, scientists revealed that the W106 and V137 related to substrate recognition (mutations in these amino acids significantly decreased the enzyme activity), and the A44, M156, and W291 residues related to the higher desaturation activity for C20 substrates (mutations in these amino acids markedly increase the conversion rate of AA).…”
Section: Catalyze Performance Of ω3-desaturasementioning
confidence: 99%
“…Substrate preference was an exciting topic determined by the structure and amino acid in the enzyme's binding site. Scientists found that Δ15-desaturase from Riftia pachyptila ( 72 ) and M. alpina ( 73 ) show a preference for C18 fatty acids, while Δ17-desaturase from Pythium aphanidermatum ( 74 ) display a higher catalytic activity for C20 fatty acids ( Table 3 ). On combining site directed mutagenesis, homology modeling, and molecular docking, scientists revealed that the W106 and V137 related to substrate recognition (mutations in these amino acids significantly decreased the enzyme activity), and the A44, M156, and W291 residues related to the higher desaturation activity for C20 substrates (mutations in these amino acids markedly increase the conversion rate of AA).…”
Section: Catalyze Performance Of ω3-desaturasementioning
confidence: 99%
“…Because of the strong preference for C18 substrates of endogenous n3Des or their limited catalytic efficiency in vivo in some oleaginous microorganisms, the newly identied D17 desaturase could be an excellent choice for genetic engineering of organisms and have great potential to be used to produce EPA and DHA. 18,22,23 In contrast to the reported soluble acyl-ACP desaturases, little is known about the structure-guiding principle involved in substrate specicity and regioselectivity of n3Des, due to lack of the three-dimensional structure information. For the rst time, the representative substrates LA-CoA and AA-CoA were chosen as the ligands, and the proposed structures of n3Des were clearly visualized based on molecular docking.…”
Section: Discussionmentioning
confidence: 99%
“…16 FADS15 and maw3 from Mortierella alpina also showed a strong preference for LA. 17,18 In 2018, two new n3Des isolated from plants -ShFAD3 from Salvia hispanica and PfFAD3 from Perilla frutescenswere used for ALA production based on their C18 substrate preference. 12 In contrast, the yeast n3Des gene Pp-fad3 isolated from Pichia pastoris GS115 showed no substrate preference with nearly the same conversion rates towards each added substrate.…”
mentioning
confidence: 99%
“…Escherichia coli DH5α, used to preserve constructed plasmids, was provided by the Culture Collection of Food Microorganisms (CCFM), Jiangnan University. PichiaPink™ Strain 2 and the plasmid pPink-HC-3CZHEK ( Wang et al, 2018 ) were purchased from Invitrogen. E. coli and P. pastoris strains were incubated at 37 °C and 28 °C, respectively, strictly following the yeast protocol from the manual (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%